A novel biomarker for marine environmental pollution of HSP90 from Mytilus coruscus. Issue 1 (15th October 2016) - Liu, Huihui; Wu, Jiong; Xu, Mengshan; He, Jianyu
Abstract: Heat shock protein 90 (HSP90) is a conserved molecular chaperone contributing to cell cycle control, organism development and the proper regulation of cytosolic proteins. The full-length HSP90 cDNA of Mytilus coruscus (McHSP90, KT946644) was 2420 bp, including an ORF of 2169 bp encoding a polypeptide of 722 amino acids with predicted pI /MW 4.89/83.22 kDa. BLASTp analysis and phylogenetic relationship strongly suggested McHSP90 was a member of HSP90 family, and it was highly conserved with other known HSP90, especially in the HSP90 family signatures, ATP/GTP-Binding sites and 'EEVD' motif. The mRNA of McHSP90 in haemolymph was upregulated in all treatments including Vibrio alginolyticus and Vibrio harveyi challenge, metals stresses (copper and cadmium) and 180 CST fuel exposure. All the results implied the expression of McHSP90 could be affected by Vibrio challenge and environmental stress, which might help us gain more insight into the molecular mechanism of HSP against adverse stresses in mollusca. Highlights: A novel HSP90 (McHSP90) was identified from Mytilus coruscus . McHSP90 significantly affected by Vibrio challenge for immune defense. McHSP90 mRNA was obviously up-regulated under stress of heavy metals and 180CST fuel. McHSP90 might be an ideal marine pollution indicator.